Fungsi dan Peran Masjid As-Sakinah dalam Meningkatkan Kehidupan Sosial dan Keagamaan Masyarakat - Hilma Nur Halimah; Hanif Rizal Ardista; Tata Aurelya Putri Virtida; Akbar Ridho Pratama; Muhammad Rizky Maulana (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
This study aims to explore the functions and roles of Masjid As-Sakinah in strengthening the social and religious life of the surrounding community. As a religious institution, the mosque holds a strategic position not only as a place of worship but also as a center of education, guidance, and community empowerment. Employing a descriptive qualitative method, data were collected through observation, in-depth interviews, and documentation involving the mosque administrators and active congregants. The findings reveal that Masjid As-Sakinah plays an effective role in spiritual development through regular activities such as Sunday Qur’an studies and the Qur’anic Education Center (TPA), which enhance religious understanding and practice among the community. In the social sphere, the mosque supports community welfare through initiatives such as the sacrificial savings program and a digital donation system using QRIS, promoting transparency and engagement. The innovative “English Massive” program illustrates the integration of education and da’wah to nurture a religious and competitive generation. Key supporting factors include visionary leadership and strong community participation, while major obstacles involve limited financial resources and the lack of youth regeneration among administrators. Overall, Masjid As-Sakinah significantly contributes to strengthening Islamic brotherhood and fostering a socially empowered and spiritually grounded community.